2013
DOI: 10.1038/bjc.2013.790
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion-weighted and multiphase contrast-enhanced MRI as surrogate markers of response to neoadjuvant sunitinib in metastatic renal cell carcinoma

Abstract: Background:Current imaging criteria for categorising disease response in metastatic renal cell carcinoma (mRCC) correlate poorly with overall survival (OS) in patients on anti-angiogenic therapies. We prospectively assess diffusion-weighted and multiphase contrast-enhanced (MCE) MR imaging (MRI) as markers of outcome.Methods:Treatment-naive mRCC patients on a phase II trial using sunitinib completed an MRI substudy. Whole-tumour apparent diffusion coefficient (ADC) maps and histograms were generated, and mean … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
25
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 39 publications
0
25
0
1
Order By: Relevance
“…Several tumor imaging characteristics may be used to assess tumor response to treatment, including assessment of tumor vascularity with dynamic contrast-enhanced techniques such as ultrasound [31], CT [32], and MRI [33]; arterial spin labeling [34]; and measuring the apparent diffusion coefficient (ADC) on DWI [35]. Validation of these methods is ongoing.…”
Section: Discussionmentioning
confidence: 99%
“…Several tumor imaging characteristics may be used to assess tumor response to treatment, including assessment of tumor vascularity with dynamic contrast-enhanced techniques such as ultrasound [31], CT [32], and MRI [33]; arterial spin labeling [34]; and measuring the apparent diffusion coefficient (ADC) on DWI [35]. Validation of these methods is ongoing.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with other histologic and clinical factors, including tumor size, microvascular invasion, necrosis, and invasion of the collecting system [8,9], high Fuhrman grade has been identified an independent risk factor for predicting metastasis after nephrectomy. Thus, preoperative characterization of the aggressiveness of clear cell RCC is vital for selecting the optimal therapy and thus helpful for improving active surveillance [10,11].DWI is gaining interest as a tool for determining localized renal mass, differentiating RCC subtypes, and predicting tumor aggressiveness [12][13][14][15][16][17]. Studies have shown differ-C lear cell renal cell carcinoma (RCC) is the most common type of primary renal malignancy in adults.…”
mentioning
confidence: 99%
“…DWI is gaining interest as a tool for determining localized renal mass, differentiating RCC subtypes, and predicting tumor aggressiveness [12][13][14][15][16][17]. Studies have shown differ-C lear cell renal cell carcinoma (RCC) is the most common type of primary renal malignancy in adults.…”
mentioning
confidence: 99%
“…Both have been previously used for the assessment of treatment response in renal cell carcinoma. [10][11][12][13][14] After less than 3 weeks of therapy, we observed a more heterogeneous ADC map with an overall decline in ADC values within the metastatic lesions. There are several explanations for this observation: sunitinib-induced coagulative necrosis may occur following the decrease of blood flow.…”
Section: Discussionmentioning
confidence: 73%